Pernikahan Perempuan Usia Dini Di Desa Beluk Raja, Kecamatan Ambunten, Kabupaten Sumenep - Zannah, Yulfa Miftahul; Kebayantini, Ni Luh Nyoman; Suka Arjawa, I Gst. Putu Bagus (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2019)
zABSTRACT This study aims to explain of early age women married to men who are much older in age and the social implementation that occurs in women who marry at an early age in Beluk Raja Village, Ambunten District, Sumenep Regency. The approach used to the type of descriptive research. The theories used in this study are the social actions of Max Weber. Social action according to Max Weber is an individual action that has a meaning or subjective meaning for himself and is associated with others. research that has been done, the reason for early age women to marry men whose age is much more Beluk Raja Village of the wishes of their parents, themselves and promiscuity. The social implication that occurs in women who get married at an early age is the acceptance of parents and attitudes of women after marriage in Beluk Raja Village, Ambunten District, Sumenep Regency. Keywords: early age marriage, woman